Stalin : an appraisal of the man and his influence : volume two : the revolutionary in power - Trotski, Leon; Malamuth, Charles (London : Panther Books, 1969)
Bibliotheek François Vercammen
Engels
Meerdelige publicatie
Keywords: Stalin, Jozef